2012
DOI: 10.1021/ac300688u
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lipids: Metal Oxide Laser Ionization Mass Spectrometry

Abstract: Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) has been used for lipid analysis; however, one of the drawbacks of this technique is matrix interference peaks at low masses. Metal oxide surfaces are described here for direct, matrix-free analysis of small (MW < 1000 Da) lipid compounds, without interferences in the resulting spectra from traditional matrix background peaks. Spectra from lipid standards produced protonated and sodiated molecular ions. More complex mixtures including veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…Previous work showed that metal oxides facilitate laser ionization to produce strong molecular ions of FAMEs [14]. Thus, NiO, MgO, SB15, and a bare MALDI plate were evaluated for matrix-free THM of tripalmitin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work showed that metal oxides facilitate laser ionization to produce strong molecular ions of FAMEs [14]. Thus, NiO, MgO, SB15, and a bare MALDI plate were evaluated for matrix-free THM of tripalmitin.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported the use of metal oxide laser ionization mass spectrometry (MOLI MS) as a matrix-free system for laser ionization of lipid materials [13,14]. Using this method, analyte ionization occurs by protonation, or sodiation due to interactions with Lewis acid/base sites on the metal oxide.…”
Section: Introductionmentioning
confidence: 99%
“…The method produced goodquality spectra down to 0.5 pmol of deposited analyte with a signal-to-noise ratio of 13, comparable to the sensitivity of reported nanostructured gold 46 and metal oxide LDI methods, 47 although a direct comparison has not been made ( Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…Many other matrix-free methods have been developed for laser desorption/ionization of small molecules, with potential applications in metabolomics. A variety of surface properties have been studied for matrix-free ionization of small molecules, for example: diamond nanowires [17] sol-gel derived silver-nanoparticles-impregnated thin biofilm [18], nanoporous gallium nitride-silver nanoparticles [19], metal oxide surfaces [20], nanofilament silicon [21], etc. Comprehensive reviews of innovative technologies using energy-absorbing materials for matrix-free LDI-MS have been recently published [22][23][24].…”
Section: Matrix-assisted and Matrix-free Laser Desorption/ionization Msmentioning
confidence: 99%